Valuing the epistemological reading in educational research - Rodrigues, Susy Cristina (Universidade Estadual de Campinas, 2014)
We have shown here the importance of studies of epistemology for questioning, deconstructing prejudices and contribution to the qualified elaboration in the production of scientific knowledge. The epistemological reading of a survey completed with the title appears: "The invented adolescence and the subjects who invent themselves in the social participation: captures and ruptures" (CAMPOS, 2008), with theoretical basis of Sánchez Gamboa (2012, 2013). At the end of this reading, after identifying the paradigmatic matrix between the construction of question and answer in this research, we propose thinking about the limits, mistakes, successes and choices in the research, based on the value of epistemology.